Editors' Note: Race-Ethnic Disparities in Rates of Declination of Thrombolysis for Stroke. (13th December 2022) - Lewis, Ariane; Galetta, Steven
Abstract : In "Race-Ethnic Disparities in Rates of Declination of Thrombolysis for Stroke, " Mendelson et al. reported that of 177, 115 tissue plasminogen activator (tPA)-eligible patients identified from a Get With the Guidelines registry, only 3.7% declined tPA over a 3-year period. Declination was more common in non-Hispanic Black patients than in non-Hispanic White patients. Patel et al. noted that it is important to recognize how clinician biases in perception and documentation could affect these observations. Ortega-Gutierrez et al. agreed that these findings may be related to provider-level factors and structural racism and emphasized the importance of identifying opportunities to address racial and ethnic disparities in stroke treatment.